2011
DOI: 10.1016/j.conb.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Long-term plasticity at inhibitory synapses

Abstract: Experience-dependent modifications of neural circuits and function are believed to heavily depend on changes in synaptic efficacy such as LTP/LTD. Hence, much effort has been devoted to elucidating the mechanisms underlying these forms of synaptic plasticity. While most of this work has focused on excitatory synapses, it is now clear that diverse mechanisms of long-term inhibitory plasticity have evolved to provide additional flexibility to neural circuits. By changing the excitatory/inhibitory balance, GABAer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
168
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(174 citation statements)
references
References 96 publications
6
168
0
Order By: Relevance
“…Inhibitory GABAergic interneurons are highly diverse in their morphological and physiological properties (29,30) and play many roles in microcircuit computation (31,32), including balancing excitation and inhibition to sustain cortical network stability (33)(34)(35)(36). This versatility is enabled in part through a diverse set of plasticity mechanisms that allow inhibition to be modulated by sensory experience (26,(37)(38)(39)(40). Hebbian (LTP and LTD) and spike-timing-dependent forms of plasticity at inhibitory synapses have been broadly described in multiple brain areas and involve numerous induction and expression mechanisms (27,37,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitory GABAergic interneurons are highly diverse in their morphological and physiological properties (29,30) and play many roles in microcircuit computation (31,32), including balancing excitation and inhibition to sustain cortical network stability (33)(34)(35)(36). This versatility is enabled in part through a diverse set of plasticity mechanisms that allow inhibition to be modulated by sensory experience (26,(37)(38)(39)(40). Hebbian (LTP and LTD) and spike-timing-dependent forms of plasticity at inhibitory synapses have been broadly described in multiple brain areas and involve numerous induction and expression mechanisms (27,37,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…We wondered whether this might reflect developmental changes in the underlying signaling pathways that trigger plasticity at this synapse. The signaling pathways responsible for plasticity at neocortical L4 FS→SP synapses are not currently known; however, some forms of neocortical LTP of inhibition depend on GABA B R signaling (26,27), whereas some forms of neocortical LTD of inhibition depend on endocannabinoid signaling (26,28). Here we asked whether L4 FS→SP plasticity is also dependent on GABA B R signaling.…”
Section: Developmental Profile Of Long-term Plasticity At Fs→sp Synapmentioning
confidence: 98%
“…Although the vast majority of work on the mechanisms and functions of LTP and LTD have focused on excitatory synapses, potentiation and depression of inhibitory transmission (I-LTP/I-LTD) can also be observed in the brain (Castillo et al 2011). The underlying molecular mechanisms of I-LTP and I-LTD are variable, but one common feature is that they are often heterosynaptic.…”
Section: Nmdar-dependent Ltp Of Inhibitory Transmissionmentioning
confidence: 99%
“…Previous studies have shown that presynaptic LTP of GABAergic synapses usually arises from a heterosynaptic mechanism that requires retrograde signaling, which is often mediated through postsynaptic NMDA receptor activation (52,53). Although glutamate is not the main excitatory transmitter in insect brains, it is likely that NMDA receptors, which typically mediate synapse plasticity rather than synaptic depolarization (54), serve evolutionarily conserved functions in synaptic plasticity (55).…”
Section: Pn-specific Nmda Receptors May Explain Odorant Selectivity Inmentioning
confidence: 99%